Does the Unique Leadership Characteristics of Olympic Athletes Enhance their Employability? - OLY, Noemi Zaharia (Journal of Sports Research, 2022)
Olympic athletes possess unique physical, mental, and leadership characteristics. Identifying and quantifying their leadership skills can enhance their employability, leading to a successful career transition. The researcher assessed 119 Olympic athletes, medalists (n =72), and non-medalists (n = 45) who competed in 11 different sports, representing both genders, various age groups, and from 20 countries, and competed in at least one Olympic game. Using the Leadership Trait Questionnaire (LTQ) survey, out of the possible 70 points, the entire population surveyed had the mean LTQ score of 62.48, medalists scored 61.49 and non-medalists scored 62.70. With no significant differences in LTQ scores, the conclusion can be drawn that all Olympians possess unique leadership characteristics. To explore how to enhance the employability of elite athletes, the researcher investigated if a correlation exists between their total LTQ scores and their chosen careers. Out of 119 participants, most remained in the sporting world as coaches (n=46), with others mostly remaining in sports related fields. The correlation between the LTQ scores and their age, gender, sports, highest placement was also analyzed. In conclusion, the employability of elite athletes can be improved by empowering them to have a better understanding of their unique leadership characteristics alongside other exceptional skills they already possess and apply them as they transition to life after sports.